The labor force cost of bearing children the motherhood wage gap in the Philippines - Duco, Alessandra Jasmine G. (School of Economics, University of the Philippines Diliman, 2018)
The gender wage gap is a widely studied phenomenon across many countries and in the Philippines, the total gap as of 2015 is negative 5.4 percent, with women earning more than men (Albert et al., 2018, p.21). Using data from the Labor Force Survey released for October 2016, this investigates the effect on education, marital status, age, number of children, and occupation on the gender wage gap. The results point to the existence of an overall wage and motherhood wage gap in the Philippines, with education and occupation being factors to the income of an individual.